Along for the ride eaudiobook - Dessen, Sarah (Recorded Books Inc., 2009)
Sarah Dessen's New York Times best-selling books are hits with young people and critics for their frank honesty and moving portraits of the teenage experience. Meet Auden, a young lady struggling with her parents' divorce. Escaping from under her demanding mother's heel, Auden goes to live with her dad in a small beach town. There she meets Eli, a loner burdened by guilt. Fellow insomniacs, they explore the town at night, discovering new ways to connect.